Pengaruh PSAK Terhadap Penyajian Pelaporan Keuangan Perusahaan Kontraktor - Carel Angelica Aulia Putri; Wahyu Helmy Dimayanti Sukiswo (Universitas 17 Agustus 1945 Jakarta, 2026)
This study aims to analyze the effect of the implementation of Financial Accounting Standards Statement (PSAK) 23 on the presentation of financial reporting in contractor companies. PSAK 23 is an important guideline in revenue recognition, especially for companies with long-term projects such as contractor companies. The method used in this study is a quantitative approach with data collection techniques through distributing questionnaires to eleven employees involved in the preparation of financial reports at PT Tirta Sarana Mulia Technology. Data processing was carried out using the WarpPLS application with the Structural Equation Modeling (SEM) method. The results of the study indicate that the implementation of PSAK 23 has a significant effect on the quality of presentation of financial reports of contractor companies. Based on the path analysis, a coefficient value of 0.750 was obtained with a T-Statistics value of 34.09 and a significance level below 0.001. The model used in this study also showed a good level of fit with the data analyzed, as indicated by the chi-square, RMSEA, and CFI values that met the standard criteria. The findings of this study confirm that the implementation of PSAK 23 can increase the transparency and accuracy of contractor companies' financial reporting, so that it can increase stakeholder trust.